2022
DOI: 10.1002/anie.202215057
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Nickel Anchored on a Nitrogen‐Doped Carbon/TiO2Composite for Efficient and Selective Photocatalytic CH4Oxidation to Oxygenates

Abstract: Direct photocatalytic oxidation of methane to liquid oxygenated products is a sustainable strategy for methane valorization at room temperature. However, in this reaction, noble metals are generally needed to function as cocatalysts for obtaining adequate activity and selectivity. Here, we report atomically dispersed nickel anchored on a nitrogendoped carbon/TiO 2 composite (NiÀ NC/TiO 2 ) as a highly active and selective catalyst for photooxidation of CH 4 to C1 oxygenates with O 2 as the only oxidant. NiÀ NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Methane oxidation by oxygen gas to C 1 oxygenates (e.g., CH 3 OH, CH 3 OOH, and HCHO) in the presence of water has been well-studied using oxide-based photocatalysts. The selectivity of products can be manipulated via the modification of different co-catalysts . For instance, a high primary products (CH 3 OOH and CH 3 OH) yield of 25.4 μmol/h and a selectivity of 95% were achieved over TiO 2 modified by Au-CoO x dual co-catalyst .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane oxidation by oxygen gas to C 1 oxygenates (e.g., CH 3 OH, CH 3 OOH, and HCHO) in the presence of water has been well-studied using oxide-based photocatalysts. The selectivity of products can be manipulated via the modification of different co-catalysts . For instance, a high primary products (CH 3 OOH and CH 3 OH) yield of 25.4 μmol/h and a selectivity of 95% were achieved over TiO 2 modified by Au-CoO x dual co-catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of products can be manipulated via the modification of different co-catalysts. 9 For instance, a high primary products (CH 3 OOH and CH 3 OH) yield of 25.4 μmol/h and a selectivity of 95% were achieved over TiO 2 modified by Au-CoO x dual co-catalyst. 10 Up to now, photocatalytic methane conversion has already been achieved over TiO 2 , ZnO, WO 3 , etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4a, and displays strong quadruple signals of ·OH (●) that were detected under illumination, 21 accompanied by recognizable ·CH 3 signals (*). 22 If methanol was used as the ·OH trapping agent, as shown in Fig. 4b, an obvious sextet ·OOH signal (marked with triangles) and a detectable ternary signal corresponding to ·CH 2 OH were detected (marked with diamonds).…”
Section: Resultsmentioning
confidence: 99%
“…16 Furthermore, the 13 C isotope labeling strategy (Figure 5c) provided additional evidence that the carbon of CO and CH 4 originated from CO 2 , rather than the self-decomposition of the catalyst. 4,12 In addition, the adsorption properties of CN-CQD for the reaction substrates were analyzed using water contact angle measurements (Figure S14) and CO 2 -temperature-programmed desorption (CO 2 -TPD, Figure 5d). The results revealed that CN-CQD exhibited a water contact Angle of approximately 17°, indicating good water wettability.…”
Section: Fabrication and Characterization Of Morphology Andmentioning
confidence: 99%